1986
DOI: 10.1152/ajpheart.1986.251.3.h496
|View full text |Cite
|
Sign up to set email alerts
|

Meclofenamate potentiates vasoreactivity to alpha-adrenergic stimulation in chronically hypoxic guinea pigs

Abstract: The aim of this study was to examine the effect of chronic hypoxia on systemic vascular reactivity and the role of prostaglandins in modulating the vascular response to chronic hypoxia. Meclofenamate, a prostaglandin synthesis inhibitor, increased the systemic vascular resistance response to the alpha-adrenergic agonist, phenylephrine, in awake, unrestrained guinea pigs exposed for 6 wk to high altitude (3,900 m), but it did not alter the response in animals kept at low altitude (1,600 m). The systemic vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…*Significant difference from control; #significant difference from normoxic CH rats. conclusion is further supported by several studies demonstrating diminished contractility in isolated vascular preparations from CH rats compared with those from control rats (4,5,8,15).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…*Significant difference from control; #significant difference from normoxic CH rats. conclusion is further supported by several studies demonstrating diminished contractility in isolated vascular preparations from CH rats compared with those from control rats (4,5,8,15).…”
Section: Discussionsupporting
confidence: 61%
“…Several groups have shown that animals exposed to CH demonstrate diminished responsiveness of the sys- temic vasculature to a variety of vasoconstrictors (5,8,14,15). Furthermore, this attenuated vasoconstriction is maintained even on acute return to a normoxic environment, as previously demonstrated in both conscious animal and isolated vascular ring studies (4,5).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Any information available on the effects of chronic hypoxaemia on peripheral vasoreactivity is conflicting. Investigators have reported both increased (Aoki & Robinson, 1969; Harrison et al 1986) and decreased (Doyle & Walker, 1991) peripheral vasoreactivity to α‐adrenergic agonists in the chronically hypoxic rat and guinea‐pig. Information on peripheral vasoreactivity in response to vasoconstrictor/vasodilator agents in either the llama fetus or the chronically hypoxic sheep fetus is not available to date.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments performed to date indicate that several different mechanisms may underlie this effect and that the mechanisms may vary between vessels taken from different anatomical sites in different species. For example, in uterine arteries of sheep, chronic systemic hypoxia was found to decrease a 1 adrenoreceptor density and agonist binding and to inhibit a 1 adrenoreceptor-contraction coupling , while in guinea-pig aorta, it was reported that chronic hypoxia increased the production of vasodilator prostanoids (Harrison et al 1990). Further, in rat aorta, the attenuated responsiveness to the a 1 adrenoceptor agonist phenylephrine (PE) induced by 48 h of systemic hypoxia was attributed to induction of endothelial haemoxygenase and the consequent enhanced production of the vasodilator, carbon monoxide (Caudill et al 1998).…”
mentioning
confidence: 99%